2005
DOI: 10.1111/j.1440-1827.2005.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KIT, EGFR, HER‐2 and tyrosine phosphorylation in undifferentiated thyroid carcinoma: Implication for a new therapeutic approach

Abstract: The KIT, epidermal growth factor receptor (EGFR) and HER-2 oncoproteins have tyrosine kinase activity and are molecular targets in human cancer therapy. To clarify the significance of KIT, EGFR, and HER-2 in undifferentiated thyroid carcinoma (UTC), the expression of these receptors and tyrosine phosphorylation was examined immunohistochemically in resected cases of UTC and papillary thyroid carcinoma (PTC). KIT, EGFR, and HER-2 were also examined at the protein and mRNA levels in five UTC cell lines. KIT expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
4
27
0
1
Order By: Relevance
“…These cells do, however, retain differentiated thyrocytic function and are responsive to growth factors. The anaplastic cell line, 8305C, was established from an undifferentiated thyroid and is positive for both EGFR and HER2 (Murakawa et al 2005). From cell cycle analysis, 8305C cells had a greater percentage of cells in the G 2 /M phase in comparison to the FTC-133 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These cells do, however, retain differentiated thyrocytic function and are responsive to growth factors. The anaplastic cell line, 8305C, was established from an undifferentiated thyroid and is positive for both EGFR and HER2 (Murakawa et al 2005). From cell cycle analysis, 8305C cells had a greater percentage of cells in the G 2 /M phase in comparison to the FTC-133 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the antineoplastic activity of CLM3, we presently investigated the effects of CLM3 in combination with SN-38 in EGFR and VEGFR-2 expressing human endothelial cell line HMVEC-d and in EGFR and RET expressing human thyroid cancer cell 8305C [50].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, EGFR and VEGFR2 overexpression has been shown to be closely correlated to advanced tumor stage, metastasis, and poor clinical outcome in several human cancers. With respect to thyroid carcinomas, EGFR overexpression has been detected in most anaplastic tumors (Schiff et al 2004, Wiseman et al 2007, Elliott et al 2008 and to a much lower extent in PTCs (Schiff et al 2004, Murakawa et al 2005, Mitsiades et al 2006, Lim et al 2007, Elliott et al 2008. In PTC, EGFR expression has been associated to poor prognosis (Akslen & Varhaug 1995, Chen et al 1999, although not always (Lim et al 2007), and recent studies have suggested that EGFR inhibitors might be active against anaplastic thyroid carcinomas (Lopez et al 2008).…”
Section: Discussionmentioning
confidence: 99%